The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1139/cjas-2019-0166
|View full text |Cite
|
Sign up to set email alerts
|

Standardized ileal digestibility of amino acids and apparent metabolizable energy in corn and soybean meal for organic broiler chicken production in Ontario

Abstract: Standardized <b>(SID</b>) digestibility of amino acids (<b>AA</b>) and apparent metabolizable energy (<b>AMEn</b>) in samples of organic corn and soybean meal (SBM) were determined. Conventional corn (<b>CC</b>) and SBM (<b>CSBM</b>) samples were tested for comparison. A total of 560, 14 d old male broiler chickens (Cobb 500) were weighed, placed in cages (10 birds/cage) and allocated to 7 (n=8) semi-purified wheat starch-based diets. Diets were: 1) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is generally accepted that corn-based diets have a superior nutritive value relative to diets based on small grains such as wheat and barley linked to higher concentration of anti-nutritive soluble fiber ( Slominski, 2011 ). However, it has also been demonstrated that the nutritional value of corn is variable and linked to the chemical composition profile ( Cowieson, 2005 ; Leung and Kiarie, 2020 ). However, since the corn used in the present study was from the same source (feed mill), it is postulated that physiological differences between broilers and turkeys could have played a part.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that corn-based diets have a superior nutritive value relative to diets based on small grains such as wheat and barley linked to higher concentration of anti-nutritive soluble fiber ( Slominski, 2011 ). However, it has also been demonstrated that the nutritional value of corn is variable and linked to the chemical composition profile ( Cowieson, 2005 ; Leung and Kiarie, 2020 ). However, since the corn used in the present study was from the same source (feed mill), it is postulated that physiological differences between broilers and turkeys could have played a part.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional SBM, corn, and wheat were procured from local feed mill (Floradale Feed Mill Ltd., Floradale, ON, Canada). The coefficients for standardized ileal digestibility of amino acids and AMEn for SPC (assumed to be equivalent to MSPC) and wheat were obtained from Evonik Aminodat 5.0 (Evonik industries, Essen, North Rhine-Westphalia, Germany) and for corn and SBM from Leung and Kiarie (2020) . Four complete starter diets were formulated: control or control plus MSPC (at 7.7, 10 or 12.5% inclusion).…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of CP in casein, SBM (hulled solvent extracted), fishmeal and BSFLM (partially defatted) were comparable with literature values ( NRC, 2012 ; Mwaniki and Kiarie, 2019 ). For feed formulation, the crude protein values for casein and FM were from book values and those of SBM and BSFLM from previous experiments from our laboratory ( Mwaniki and Kiarie, 2019 ; Leung and Kiarie, 2020 ). With exception of casein diet, there were discrepancies between formulated (∼10% CP) vs. analyzed dietary CP.…”
Section: Resultsmentioning
confidence: 99%